Travelling wave ion mobility and negative ion fragmentation for the structural determination of N‐linked glycans. Issue 16 (22nd July 2013) - Harvey, David J.; Scarff, Charlotte A.; Edgeworth, Matthew; Crispin, Max; Scanlan, Christopher N.; Sobott, Frank; Allman, Sarah; Baruah, Kavitha; Pritchard, Laura; Scrivens, James H.; Guttman, Andras
<x xml:space="preserve">Abstract</x> Travelling wave ion mobility was investigated for its ability to separate N‐glycans from other compounds and for resolution of isomers. Charged glycans, exemplified by sialylated complex N‐glycans released from bovine fetuin and ionised by electrospray, could be separated from residual glycopeptides allowing the minor, more highly sialylated compounds to be detected where their ions were obscured by ions from other compounds in different charge states. This technique was also found to be excellent for extracting the N‐glycan profiles from contaminated samples. Structural identification of the glycans was performed by negative ion CID fragmentation, a method that provides a wealth of structurally diagnostic ions. However, fragment ions can also appear in the glycan profiles where they can be mistaken for glycan molecular ions. Fragments and molecular ions were frequently shown to have different drift time profiles, allowing them to be differentiated. Some separation of isomers was found but only for the smallest compounds. Differentiation from conformers was achieved by plotting drift time profiles of the fragments; these profiles matched those of the precursor ions where conformers were present. The techniques were applied to investigations of N‐glycans released from the fungus Piptoporus betulinus where the technique was used to separate different carbohydrate types present in biological extracts.